Review On Carbon Nanotube Based Polymer Composites And Its Applications - Abd Razak, Jeefferie; Noor, N. A.M.; Ismail, Syahriza; Mohamad, Noraiham; Lau, Kok Tee; Munawar, Rose Farahiyan; Junid, Ramli (Universiti Teknikal Malaysia Melaka, 2018)
The unique structural,electrical and mechanical properties of carbon nanotubes (CNTs) appoint CNTs as a promising candidate for a broad advantage on the applications of sensors,electronic devices,biomedical and many more.Due to the problems in transferring the extraordinary properties of CNTs to the application,it is critical to modify CNT surface before starting with further experimental procedure in order to improve interfacial adhesion,strength and mechanical properties of polymer/CNTs.This short review provides an overview of the state of knowledge especially in dispersion method, applications and recent research on CNTs with a particular emphasis on CNTs as reinforcement of polymer composites,for many potential applications.